RANCANG BANGUN DAN ANALISIS HEAVY DUTY HAND TRUCK DENGAN METODE ELEMEN HINGGA - Stephen Owen Hizkia; Toni Prahasto; Djoeli Satrijo (JURNAL TEKNIK MESIN, 2023)
Hand truck is one of material handling equipment used to transport and move material in industry. Some cases in the industrial settings, hand truck with a high loading capacity or used to be called a heavy duty hand truck is needed. The purpose of this research is to design and analyze hand truck with a distributed loading capacity of 15 tons. The design, simulation and analysis processes in this study use Solidworks 2020 and Ansys 2020 R1 software. The hand truck is designed to adopt the heavy duty hand truck model that has been circulating in the market. Then a static analysis using the finite element method on the hand truck frame is carried out to ensure that the structure and materials used are able to withstand loading. Static analysis shows the value of deformation, stress, strain, and factor of safety on the hand truck frame. With a factor of safety value above 1, it shows that the stress experienced on the hand truck frame is below the maximum stress allowed by the material and the hand truck frame is able to withstand the target loading. After that, a simple kinematics and dynamics analysis using the motion study in the Solidworks was carried out to show the conditions experienced between wheels and surface.